Effectiveness Of Chest X-Ray in Diagnosing Pulmonary Oedema in Pregnancy: A Case Report - Mathias; Risna Ulinawaty Pasaribu B.; Surya Waisnawa; Theresia Euralia Pasaribu; Verine Angeline (Medical Clinical Update, 2023)
Almost every pathology condition involved heart and lung use chest x-ray as a diagnosticmethod, with no exception in pregnant woman. One of the most common abnormalities found inthe lung is pulmonary oedema. Pulmonary oedema is a condition caused by the accumulation offluid in the interstitial spaces and alveoli of the lung. Pulmonary oedema is distinguished by cardiogenic and noncardiogenic causes. Cardiogenic pulmonary oedema is caused by left heartfailure regardless of the reason. Non-cardiogenic pulmonary oedema caused by underlying diseases besides the heart. The important radiological features in pulmonary oedema are the thickening of the interlobar septa, commonly called the septal line or Kerley line, peri bronchial cuffs,fluid in the fissures and pleural effusion. Interlobar septa are usually not visible on a chest x-ray.This septa will be visible if there is a build-up of fluid in the area. Management of patients withpulmonary oedema is to improve the airway, adequate ventilation, and oxygenation.